2021
DOI: 10.1186/s13256-021-03013-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in ACADVL causing very long-chain acyl-coenzyme-A dehydrogenase deficiency in a South Asian pediatric patient: a case report and review of the literature

Abstract: Background Very long-chain acyl-coenzyme-A dehydrogenase deficiency is a rare, severe life-threatening metabolic disorder of mitochondrial fatty acid oxidation, caused by mutations in ACADVL gene. Here we present a genetically confirmed case of a South Asian baby girl with severe, early-onset form of very long-chain acyl-coenzyme-A dehydrogenase deficiency due to a novel mutation in ACADVL gene. Case presentation Index case was the second baby girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…ACADL plays an important role in the β oxidation of long-chain fatty acids, and its deficiency or deletion will cause mitochondrial dysfunction and then affect lipid metabolism [ 41 ]. ACADVL and ACADM genes can participate in biological processes related to lipid metabolism, affect the synthesis and decomposition of fatty acids and glycerol, and play a vital role in lipid metabolism [ 42 , 43 , 44 ]. The low expression of CPT1A affects the fatty acid metabolism of BMECs and inhibits the synthesis and accumulation of cellular lipids, which is also consistent with the result that the overexpression of xeno-miR168b inhibits fatty acid production.…”
Section: Discussionmentioning
confidence: 99%
“…ACADL plays an important role in the β oxidation of long-chain fatty acids, and its deficiency or deletion will cause mitochondrial dysfunction and then affect lipid metabolism [ 41 ]. ACADVL and ACADM genes can participate in biological processes related to lipid metabolism, affect the synthesis and decomposition of fatty acids and glycerol, and play a vital role in lipid metabolism [ 42 , 43 , 44 ]. The low expression of CPT1A affects the fatty acid metabolism of BMECs and inhibits the synthesis and accumulation of cellular lipids, which is also consistent with the result that the overexpression of xeno-miR168b inhibits fatty acid production.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an acute clinical presentation prior to availability of screening results, or lack of newborn screening in some reported cases, it may not be possible to implement intervention. 17 , 18 , 19 However, intervention with dextrose containing intravenous fluids and MCTs may alter the prognosis if initiated early enough postnatally. 16 Scalais et al reported a family in which the first two children died of sudden unexplained cardiopulmonary arrest at less than 36 hours of age.…”
Section: Discussionmentioning
confidence: 99%